Clinicopathological Spectrum of Thyroid Swelling: A Single Institutional Prospective Study from Northeast India - Daimary, Michimi; Choubey, R N; Nath, Jyotiman (Asian Pacific Journal of Cancer Care, 2023)
Purpose: The pathologic lesions of the thyroid gland are manifested by varied morphologies. The current study aims to report the clinicopathologic features of patients with thyroid swelling from a tertiary centre of North-East India with particular emphasis on histopathological examination (HPE). Method: It is a prospective hospital-based study. Fifty-three resected specimens of thyroid surgery were included in the study. All the specimens were undertaken for HPE, and the malignant cases were subjected to immunohistochemistry (IHC). Results: Female preponderance (84.9%) of the disease was found with a maximum incidence between the age group younger than 40 (60.37%). 86.8% of cases were benign on HPE; colloid goitre reported a maximum number (62.3%). Only seven cases were found malignant, and six out of them were papillary carcinoma. All the six papillary carcinomas and one follicular carcinoma showed immunoreactivity of tumour cells to TTF 1, CK 7 and Thyroglobulin. Conclusion: Asymptomatic thyroid swelling is a prevalent entity, and the incidence of malignancy in the current study is 13.2%. Identifying malignant thyroid swelling out of the common benign or apparently benign goitres has always been problematic, and preoperative fine-needle aspiration cytology followed by HPE and IHC plays a significant role.